2019
DOI: 10.14221/ajte.2018v44n6.3
|View full text |Cite
|
Sign up to set email alerts
|

Does a “Science, Technology and Social Change” Course Improve Scientific Habits of Mind and Attitudes towards Socioscientific Issues?

Abstract: The study aimed at exploring whether a "Science-Technology-Social Change" course improved pre-service social studies teachers' (PST) scientific habits of mind and attitudes towards socio-scientific issues. Within a pre-and post-course experimental design, the study was conducted with 135 second-year PST (68 males and 67 females) from two classes at Department of Social Studies Teacher Education in a large-size university, Turkey. Two different Likert type scales, Scientific Habits of Mind Scale and Attitudes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
(36 reference statements)
2
10
0
2
Order By: Relevance
“…That is, if much more evidence is provided, they may alter their beliefs and/or worldviews . In other words, concept cartoons may afford students to evolve their scientific habits of mind (i.e., open-mindedness), which is a milestone for scientific attitude, nature of science, scientific inquiry and scientific literacy (e.g., Çalık & Coll, 2012;Çalık, Turan & Coll, 2014;Çalik & Karataş, 2019). Overall, producing their own arguments through concept cartoons may increase students' awareness levels of conceptual scaffolds and knowledge construction (Chin & Teou, 2009).…”
Section: Abstract: Concept Cartoon Informal Learning Initial Impresmentioning
confidence: 99%
“…That is, if much more evidence is provided, they may alter their beliefs and/or worldviews . In other words, concept cartoons may afford students to evolve their scientific habits of mind (i.e., open-mindedness), which is a milestone for scientific attitude, nature of science, scientific inquiry and scientific literacy (e.g., Çalık & Coll, 2012;Çalık, Turan & Coll, 2014;Çalik & Karataş, 2019). Overall, producing their own arguments through concept cartoons may increase students' awareness levels of conceptual scaffolds and knowledge construction (Chin & Teou, 2009).…”
Section: Abstract: Concept Cartoon Informal Learning Initial Impresmentioning
confidence: 99%
“…Management System has been committed to be used as vehicle to promote critical thinking skill (Alsaleem, 2013;Gharib, et al, 2016;Ta'amneh, 2017;Çalik, & Karataş, 2019;Zaenudin, et.al., 2019). The study also might be illuminating for the teachers to heighten their sense of the importance of E-writing as a prominent strategy (Kavaliauskienė, et al, 2013) to increase students' critical thinking.…”
Section: What Does the Results Imply?mentioning
confidence: 99%
“…For instance, they used SSIs like alternative treatment and vaccination to investigate mistrust of the argument from the authority, issues about rainforests and biodiversity, and overhead power lines to explore rationality, using issues about nutrition, energy sources, and climate change to measure openmindedness. In addition, previous studies showed that using SSIs as a way to examine students' SHOM became a useful study for exploring students' decision-making about SSIs (e.g., Çalik et al, 2014;Çalik and Karataş, 2019).…”
Section: Socio-scientific Issue and Students' Scientific Habits Of Mindmentioning
confidence: 99%
“…Students have been familiar with inquiry-based learning but they not familiar yet with the presence of SSIs. Meanwhile, SSIs significantly contribute to students' SHOM (Çalik and Karataş, 2019). Therefore, the use of inquiry learning that combines with SSIs strongly contributes to the development of students' SHOM (Grooms et al, 2014).…”
Section: Glass Cleanermentioning
confidence: 99%
See 1 more Smart Citation